Zygoma Bone Shell Technique: A Proof‐of‐Concept Surgical Protocol in Human Cadaver for Bone Reconstruction After Zygomatic Implant Failure - Agliardi Enrico Luigi; Pozzi Alessandro; Gherlone Enrico (Clinical and Experimental Dental Research)
ABSTRACT Objectives This article aims to present a proof‐of‐concept surgical technique for immediate reconstruction of zygoma anatomy following implant failure and complications, illustrating the related clinical steps in a cadaver specimen. Zygomatic implants represent a paradigm shift, addressing challenges posed by severe maxillary bone atrophy and partial or complete maxillectomy, not suitable for conventional dental implant placement. Despite documented high survival rates, intra‐ and postoperative complications can occur and lead to implant failure, resulting in severe defects extended up to entire height of zygomatic bone pyramid. Such defects may infringe immediate or delayed new implant placement, requiring complex surgical procedures to restore integrity of zygomatic bone anatomy. Material and Methods The three‐dimensional reconstruction of zygomatic bone defect was achieved by specific form of guided bone regeneration or shell technique, using a thin cortical plate harvested from external oblique line of the mandible. After a meticulous mechanical debridement of bone defect resulting from implant removal, a thin cortical bone block was harvested from the mandibular ramus. The cleared bone defect was filled with autogenous bone chips and thin bone shell was secured above with a bone fixation screw. Results Zygoma Bone Shell technique was able to restore contours of zygomatic pyramid ridge. The comparable composition between mandibular and zygomatic bone, particularly in the cortical region allowed an anatomical resemblance that facilitates optimal structural compatibility, fostering seamless integration of bone graft into zygomatic area. Conclusions Within limitations of this proof‐of‐concept, zygoma bone shell technique may offer a viable surgical procedure for immediate bone reconstruction after zygomatic implant failure. Translating the previously reported clinical outcomes of bone shell technique, it may be used same day of failing implant removal to achieve reconstruction of zygomatic anatomy with limited risk of postoperative complications. Further clinical studies are needed to confirm its predictability, reliability and anticipated benefits.